Agir mais ne rien changer ? De l’utilisation des expériences pilotes en gestion de l’environnement - Raphaël Billé (VertigO)
One of the most common approaches to environmental action consists in designing and implementing pilot experiments which aim at testing new practices and organisations. These technical or socio-political innovations are then supposed to spread. However, the way such a juxtaposition of experiments is expected to lead to a global transformation of our development paths and of their environmental dimension remains quite mysterious, if not mythified. Analysing the pilot approach as a strategy of change, this article offers a concise view on what is at stake in the replication hypothesis underlying the approach.